What does the relationship among unit trust funds indicate about optimal portfolio investment diversification strategy? Case of the Malaysian Islamic unit trust funds industry - Othman, Anwar Hasan Abdullah; Abdul Aziz, Hassanuddeen; Kassim, Salina (Institutional Investor LLC, 2017)
In the Malaysian unit trust funds (UTFs) industry, the performance of funds is often below the market portfolio and risk-free returns, as the fund managers in Malaysia show poor selectivity performance and lack of timing skills. Individual investors, therefore, need to build and diversify their portfolio investment beyond the fund managers’ portfolio for further risk mitigation and return enrichment. This study investigates the long- and short-run relationships among all net asset values (NAV) of Islamic UTFs in Malaysia over the period from April 2006 to December 2015, using the Johansen–Juselius cointegration test and vector error correction model (VECM) framework. The overall results show that the NAV of all Islamic funds share a long-run equilibrium relationship in Malaysia. On the other hand, the Engle and Granger causality test found that the Malaysian UTFs industry is an inefficient market and experiences predictable behaviors in the short run. The study, therefore, will contribute to both investors and policymakers. Investors (unit holders) could strategize and diversify their portfolio in the long run based on the degree of relationship among all the Islamic funds to achieve better risk–return trade-offs. In the short run, the result may help them predict the behavior of the funds’ NAV in the near future. For policymakers, the Securities Commission of Malaysia, and the Federation of Malaysian Unit Trust Managers can gain enormous advantages to further improve the UTFs industry by focusing on market price efficiency and a robust regulatory framework of portfolio diversification strategies for each type of fund to be more flexible and to help in eliminating such restrictions on fund managers’ operation diversification for improving UTFs returns to align them with the experience of the developed market.